Chartered status and public relations' struggle for legitimacy. (24th July 2020) - Gregory, Anne
Abstract : Purpose: To appraise progress towards "the professional project" for the public relations profession in the UK using the Royal Charter application as a pivotal assessment point in the journey. Design/methodology/approach: Primary and secondary, qualitative research, with participant observation and chronological and thematic analysis of archival documents at the time of the Charter process: 2003 to 2005. Two expert interviews were also conducted for a view on progress. The study is contextualised within the professions literature and the 2019 State of the Profession study undertaken by the Chartered Institute of Public Relations. Findings: The Institute faced significant challenges during the Charter application raised by Institutions such as the Government Department for Education and Skills, including the diversity of the profession, standards of education and training, practitioner standards, including ethical, as indicated by their levels of membership and commitment to ongoing professional development. These challenges remain. Research limitations/implications: Diversity, social acceptance, qualifications and professional progress provide an important, ongoing research agenda. Practical implications: Social acceptance, qualifications and professional progress remain elusive for the practice and more radical action is required to achieve progress. Social implications: The profession is making limited progress towards legitimacy. Continued press ambivalence, recent scandals, such as the Bell Pottinger affair in South Africa and jurisdictional infringement by other professions continue to threaten its attempts to move towards social closure. Originality/value: This is the first academic article to chronicle the charter journey using the original documentation as source materials and the first to review progress towards the goals that chartered status signified for public relations.